Inflammatory leukocyte infiltration in focal cerebral ischemia: Unrelated to Infarct Size - Faßbender, Klaus; Ragoschke-Schumm, Andreas; Kühl, Sandra; Szabo, Kristina; Fatar, Marc; Back, Walter; Bertsch, Thomas; Kreisel, Stefan H.; Hennerici, Michael G. (Cerebrovascular diseases, 2002)
Objective: An inflammatory host response in the ischemically injured brain is well documented. However, its pathophysiological relevance is uncertain. We investigated whether inflammatory leukocyte response in the ischemic brain alters infarct size. Methods: The cellular inflammatory response to cerebral ischemia in Wistar-derived rats induced by the transient occlusion of the middle cerebral artery with a thread was pharmacologically upmodulated by lipopolysaccharide (LPS) or downmodulated by continuous infusion of carboxylated sialyl Lewisx (sLex). The effects of such experimental modulation of focal cerebral leukocyte recruitment on the extent of the resulting infarction were assessed. Results: Compared to control treatments, LPS strongly enhanced (540.5 ± 504.8 vs. 94.6 ± 60.6, p < 0.01) and sLex decreased (32.8 ± 29.1vs. 97.0 ± 49.7, p < 0.05) the numbers of neutrophils at the investigated sites in cerebral ischemia. Unexpectedly, despite such marked experimental modulation of leukocyte infiltration in the ischemic brain, the extent of the resulting cerebral infarction (percent of total hemisphere) remained unchanged under these different conditions (54.5 ± 10.8vs. 53.0 ± 19.1, n.s. and 50.3 ± 18.0 vs. 57.2 ± 10.0, n.s., respectively). Conclusions: The striking dissociation between the massively altered inflammatory leukocyte infiltration in the ischemic brain and the unchanged infarct outcome indicates that intracerebral inflammatory leukocyte recruitment is not a major pathogenic factor in the development of ischemic tissue damage.
Gesehen am 31.03.2021